2018
DOI: 10.1186/s12872-018-0807-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity score is associated with cardiovascular risk factors and serum adiponectin concentrations in patients with metabolic syndrome

Abstract: BackgroundMetabolic syndrome is associated with cardio-metabolic risk factors and lipid abnormalities. Previous studies evaluated the dietary habits and nutrient intakes among patients with metabolic syndrome; however the association between metabolic risk factors and adiponectin with dietary diversity score (DDS) in patients with metabolic syndrome has not been evaluated yet. Therefore the aim of the current study was to evaluate these relationships among patients with metabolic syndrome.MethodsOne hundred si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
4
39
1
2
Order By: Relevance
“…Logo, a adoção de hábitos de vida considerados saudáveis, como prática regular de DISCUSSÃO Neste estudo, as intervenções em grupo e individual mostraram efeito na redução do IC-1 em indivíduos com SM. Assim, o impacto positivo reforça a importância da modificação do estilo de vida na prevenção, controle e tratamento dos fatores de risco cardiometabólicos, conforme também relatos na literatura [22][23][24][25][26] .…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…Logo, a adoção de hábitos de vida considerados saudáveis, como prática regular de DISCUSSÃO Neste estudo, as intervenções em grupo e individual mostraram efeito na redução do IC-1 em indivíduos com SM. Assim, o impacto positivo reforça a importância da modificação do estilo de vida na prevenção, controle e tratamento dos fatores de risco cardiometabólicos, conforme também relatos na literatura [22][23][24][25][26] .…”
Section: Conclusãounclassified
“…Assim, estes achados demonstram que uma alimentação equilibrada e a adesão a uma vida fisicamente ativa são metas fundamentais para indivíduos com SM e constituem dois eixos fundamentais no processo de modificação do estilo de vida para a melhora dos fatores de risco modificáveis para DCV 22,26 . Estudos têm comprovado que o exercício físico possui um importante papel na manutenção da estrutura e função vascular 8 , e a inadequação alimentar já se mostrou impactar de forma significativamente negativa sobre mortalidade cardiovascular 8,24,27 .…”
Section: Conclusãounclassified
“…It refers to the nutritional adequacy and dietary diversity so that a higher DDS indicates a more protective effect against CVDs [15]. It has been shown that there was a strong correlation between dietary diversity and the arterial wall index, as well as the prevalence of HBP and obesity [15,16]. The dietary diversity assessment in children to reduce HTN complications should be critically conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence of the research results with use of this questionnaire, lets us to consider it as useful measurement tool, which is reliable source of information about frequency and quantity of food customarily consumed [24]. That's why in foreign literature similar questionnaires constitute commonly used research tool [1,5,14,25].…”
Section: Discissionmentioning
confidence: 99%